First, we will distribute the 3 on the left side of the equation:
-5x + 3x + 6 = 20
Next, combine like terms on the left side of the equation:
-2x + 6 = 20
Subtract 6 from both sides of the equation:
-2x = 14
Finally, divide by -2 to solve for x:
x = -7
The property used in each step is the distributive property.
Enter your answer and show all the steps that you use to solve this problem in the space provided. Write the steps in solving −5x+3(x+2)=20−5x+3(x+2)=20 . Justify each step with an appropriate property. (4 points)
1 answer